Effect of different diets on growth performance, physiological response and behavior of spiny lobster Panulirus homarus (Linnaeus, 1758) - Arief Rahman Rivaie; Yudha Trinoegraha Adiputra; Agus Setyawan; Dwi Handoko Putro (Universitas Diponegoro, 2023)
This study aimed to know the effect of different feedings on growth performance, physiological responses, and behavioral changes of juvenile spiny lobsters. The experimental method used a completely randomized design with three treatments and four replications. There were three different feeds used as treatment, namely: flesh mussel (K), commercial fish feed (I), and commercial shrimp feed (U). Feed is given as much as 30% of body weight, five times per day at 6:30 am, 12:00 pm, 4:00 pm, 9:00 pm, and 2:00 am. The results showed that the commercial feeding of fish (I) significantly (P<0.05) increased the survival rate and biomass of spiny lobster for 54.17% and 141.7 g, respectively. While fresh mussel give better growth and stress response, but had the lowest survival rate. The results of the physiological response test of lobster were more effective in suppressing lobster stress levels than other treatments (P<0.05). The behavior of juvenile spiny lobsters showed a very striking color difference and reflex impairment scores, which indicated that the vitality of the treated juveniles (I) was better than the vitality of the treatments (K) and treatment (U). This study shows that commercial fish feed (I) is recommended for maintaining spiny lobsters in the juvenile phase, although it needs further maintenance by using an appropriate feed formulation to improve the growth performance of spiny lobsters.